Efficient Static Analysis of Assemblies of Beam-Columns Subjected to Continuous Loadings Available as Digitized Records - Soroushian, Aram; Farahani, Emadoddin Majdabadi (Frontiers in Built Environment, 2019)
Beams, beam-columns, columns, and frames, are of major importance in structural engineering, and especially buildings and infrastructures analysis and design. In some cases, these structural members are subjected to static loadings, that though are continuous with respect to the longitudinal axes, are available as digitized records. Finite element analysis of assemblies of these members may be computationally expensive when the loading is digitized densely. In order to reduce this computational effort, attention is paid to a technique originally proposed for reduction of computational effort in seismic analysis of structural systems. In view of the convergence-based nature of this technique, in this paper, the technique is adapted to static analysis of assemblies of beam-columns subjected to digitized loadings. The good performance of the adapted technique is demonstrated from different points of view, and is compared with the performance of the technique in time integration analysis.